Hospital-based Perinatal Outcomes and Complications in Teenage Pregnancy in India - Mukhopadhyay, Prianka; Chaudhuri, RN; Paul, Bhaskar (Journal of Health, Population and Nutrition, 2010)
Teenage pregnancy is a worldwide problem bearing serious social and medical implications relating to maternal and child health. A cross-sectional observational study was undertaken to compare the different sociodemographic characteristics and perinatal outcomes of teenage primigravida mothers with those of adult primigravida mothers in a tertiary-care hospital in eastern India. A sample of 350 each in cases and comparison group comprised the study subjects. Data were collected through interviews and by observations using a pretested and predesigned schedule. Results revealed that the teenage mothers had a higher proportion (27.7%) of preterm deliveries compared to 13.1% in the adult mothers and had low-birthweight babies (38.9% vs 30.4% respectively). Stillbirth rate was also significantly higher in teenage deliveries (5.1% vs 0.9% respectively). The teenage mothers developed more adverse perinatal complications, such as preterm births, stillbirths, neonatal deaths, and delivered low-birthweight babies, when compared with those of the adult primigravida mothers. Teenage pregnancy is still a rampant and important public-health problem in India with unfavourable perinatal outcomes and needs to be tackled on a priority basis. Key words: Cross-sectional studies; Delivery, Obstetric; Observational studies; Pregnancy outcomes; Pregnancy in adolescence; India DOI: 10.3329/jhpn.v28i5.6158 J HEALTH POPUL NUTR 2010 Oct;28(5):494-500